Seßhaftwerdung von Beduinen in Kuwait - Scholz, Fred (ERDKUNDE, 1975)
There are as yet no authoritative works on the changes in nomadic (Bedouin) life styles in the states of the Persian/ Arabian Gulf in consequence of their recent economic upswing. The author uses the example of Kuwait to report on and describe the size, background and forms of settlement of the Bedouin. Even in the financially strong Gulf states the step for a Bedouin from a tent to an urban dwelling, from an unrestricted to a restricted economic existence does not occur suddenly but is part of a continuous socialisation process. The results in Kuwait are exemplary and worthy of attention.